INFORMATIZATION AND INNOVATIONS WITHIN THE EDUCATIONAL AND RESEARCH ACTIVITIES OF UNDERGRADUATES AND GRADUATE STUDENTS IN A PEDAGOGICAL UNIVERSITY - V V Grinshkun (RUDN Journal of Informatization in Education, 2016)
The article is based on the idea that innovations and informatization can become significant factor of integration of scientific and educational activity of undergraduates and graduate students in a pedagogical university.